On Satnoianu-Wu’s Inequality - Bo-Yan Xi (The Scientific World Journal)
By applying techniques in the theory of convex functions and Schur-geometrically convex functions, the author investigates a conjecture of Satnoianu on an algebraic inequality and generalizes some known results in recent years.